Concerning the "Warm Stream" within Marxism. Issue 1 (2nd January 2016) - Boer, Roland
ABSTRACT: Marxism is well known for its two components: a "cold stream" which concerns objective scientific analysis; and a "warm stream" that concerns enthusiasm and hope and leads to commitment to Marxism as a cause. Ideally, they engage dialectically with one another. They are distinct, yet they necessarily interact to produce the richness of Marxism. My focus is primarily the warm stream, which continually reappears when the "cold stream" dominates. With an overwhelming focus on objective scientific analysis and on what is possible in the given circumstances, it risks confusing the final goal for short-term achievement and failing to inspire those who wish to identify with Marxism. At those times we find that the renewal of Marxism comes from the warm stream, with efforts to bring enthusiasm and hope back into Marxism. In order to understand this process, this article analyses some earlier historical examples of such renewal. It begins by dealing with the criticisms of utopian socialism in Marx and Engels, since this had a significant effect on the way the warm stream was subsequently perceived. Then the article analyses the contributions of Anatoly Lunacharsky before the Russian Revolution and Ernst Bloch in Western Marxism. The unexpected dimension of their work was to draw upon the religious revolutionary tradition as one source for the warm stream of Marxism.